Experimental study of the corrugated structure of film packing on thermal and resistance characteristics of cross-flow cooling tower. (February 2023) - Zhao, Zefang; Gao, Jingpu; Zhu, Xiaojing; Qiu, Qinggang
Abstract: As the core component of cooling towers, packing directly affect the operation efficiency of cooling tower, so it is of great significance to optimize the structure of packing. In this paper, based on commercial corrugated packing of cross-flow cooling towers, five kinds of packing added small grooves of different directions and numbers were made to investigate their influences on the cooling performance of cooling towers. Experimental and comparative research in terms of thermal and resistance characteristics for six types (including original packing) of film packing was proposed. Also, the cooling performance of original packing and optimum packing was verified and compared in an actual cooling tower. The obtained results indicate that the parallel small grooves indeed change the cooling capacity and efficiency of packing whereas the regularity is uncertain and the crossed small grooves clearly reduce the cooling performance of packing. The resistance results show that the effect of small grooves on pressure drop is very weak for film packing. The cooling capacity of packing is improved by 3.8% ∼ 12.2% for the optimum packing. Besides, the empirical formulas of thermal and resistance characteristics for different types of packing are determined as a guide for the use of packing in cooling towers. Highlights: Parallel grooves change the cooling performance of cross-flow packing. Crossed grooves reduce the cooling performance of cross-flow packing. Small grooves have no effect on cross-flow packing resistance. The thermal and resistance correlations for packing with different grooves are proposed.